Pengaruh Implementasi Kebijakan Reformasi Birokrasi Terhadap Efektivitas Organisasi (Suatu Studi Di Sekretariat Daerah Kabupaten Halmahera Utara). - Kori, Olivia Ekstevani; Sondakh, Telly; Laloma, Alden (Sam Ratulangi University, 2015)
Abstract: This research dotted from the initial observation that the effectiveness of the organization'sSecretariat indicated area of North Halmahera Regency is still relatively low. This condition is presumablyrelated to policy implementation resformasi bureaucracy that has not gone well. Thus, this study aims: